PROBLEM-BASED LEARNING: CONCEPT AND METHOD - Marly Cruz Gomes Pinto, Maria (Revista Gênero e Interdisciplinaridade, 2022)
The main theme of this article is the Problem Based Learning methodological approach created in European universities and currently analyzed as a possibility of implementation in Brazilian basic education. The article aims to trace a history of this method, showing the usage models and finally considering its advantages and disadvantages. Using BORGES (2014) and MORAN (2015) as a theoretical basis and quotes from McMaster’s original model for a complete explanation of the topic, the article describes, from the perspective of active methodologies, the importance of problem-based learning.